PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK MENGACU PADA TAKSONOMI BLOOM UNTUK MENGUATKAN KEMAMPUAN BERPIKIR MATEMATIS - Misnati Misnati; Mohamad Rif’at; Dede Suratman (Universitas Tanjungpura, 2021)
AbstractThe general objective of this study is to determine the feasibility of the developedLKPD which refers to Bloom's Taxonomy to strengthen the ability to thinkmathematically in relation material. Research and Development (R&D) form. Thedevelopment model uses the ADDIE model. Data collection techniques in the form ofquestionnaires and validation. The results of the research show that the results of thedevelopment of the LKPD use the bloom taxonomy that this LKPD strengthens theability to think mathematically because besides being in accordance with the learningobjectives to be achieved and this LKPD contains indicators that are in Bloom'sTaxonomy.Keywords: Bloom's Taxonomy, Development, LKPD, Thinking AbilityMathematical